A meta-analysis of community engaged learning and thriving in higher education - Guanlao, Rachel; Pax, Jennifer; Wei, Yufeng; Zhang, Wei (Frontiers in Education, 2025)
IntroductionCommunity Engaged Learning (CEL) is recognized for its positive impact on student development in higher education. This meta-analysis examined the effects of CEL on academic, personal, social, and citizenship outcomes among college students.MethodsStudies were identified through PsycINFO, PsycArticles, and ERIC, and were included if they met the following criteria: peer-reviewed English-language publications from 2017 to 2024, alignment with widely accepted definitions of CEL, inclusion of a control group, and sufficient data to calculate effect sizes. Random-effects models were used to estimate Hedges's g, a standardized measure of effect size, for each outcome domain.ResultsOur results showed that CEL had a statistically significant, small to medium effect on academic outcomes (Hedges's g = 0.344, 95% CI [0.190, 0.497], p < 0.001) and social outcomes (Hedges's g = 0.371, 95% CI [0.167, 0.575], p < 0.001). The effect on citizenship outcomes was small but significant (Hedges's g = 0.220, 95% CI [0.096, 0.344], p = 0.001). For personal outcomes, the effect was moderate (Hedges's g = 0.694, 95% CI [−0.089, 1.477]) but not statistically significant (p = 0.082). The substantial variability observed across studies suggests that differences in CEL implementation, program focus, and student populations may influence outcomes.ConclusionOverall, our findings highlight CEL as an impactful pedagogy that contributes to academic success, personal growth, and civic engagement. Further research may explore the long-term impacts of CEL and identify specific program components that enhance its effectiveness.